Clinical characteristics of cystic encephalomalacia in children - Fan, Lijuan; Feng, Lianying; Gan, Jing; Luo, Rong; Qu, Haibo; Chen, Xiaolu (Frontiers in Pediatrics, 2024)
Purpose: To investigate the primary causes and clinical characteristics of cystic encephalomalacia (CE) in children. Methods: The clinical data of 50 children who were admitted to our hospital due to CE between January 2008 and December 2020 were retrospectively reviewed. Their primary causes, clinical manifestations and cranial magnetic resonance imaging features were analyzed. Results: Among all patients, 5 had prematurity, 19 had hypoxic-ischemic encephalopathy (HIE), 13 had intracranial infection, 14 had traumatic brain injury and hemorrhage, 4 had cerebral infarction, 2 had congenital genetic diseases, and 1 had hypoglycemia. The average time from primary disease onset to CE diagnosis was 70.1 ± 61.0 days. The clinical manifestations included speech or motor developmental delay (n = 33), epilepsy (n = 31), dystonia (n = 27), limb paralysis (n = 16), and visual or auditory impairment (n = 5). Patients with HIE as the primary cause of CE had a significantly higher occurrence of dystonia, while a significantly higher incidence of paralysis was observed in those with cerebral infarction as the primary cause. Conclusion: CE in children is mainly caused by HIE, intracranial infection, and cerebral hemorrhage. The major clinical manifestations included speech or motor developmental delay, epilepsy, and dystonia. Magnetic resonance imaging is an important tool for the diagnosis of CE.